Question and answer
Question not found
Ask a question
Not a good answer? Get an answer now. (Free)
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
How were the islands of Japan formed? a. By underwater volcanoes c. By strike-slip faulting b. By mid-ocean ridges d. by anticline folding
Weegy: The islands of Japan were formed by a. By underwater volcanoes (More)
Question
Expert Answered
Asked 10/17/2013 7:48:19 AM
0 Answers/Comments
____________ occurs when heat is transferred into an object through motion or movement; an example would be boiling water. a. conduction c. convection b. radiation d. heat
Weegy: c. convection occurs when heat is transferred into an object through motion or movement; an example would be boiling water. (More)
Question
Expert Answered
Asked 10/18/2013 9:36:35 AM
0 Answers/Comments
How does the position of a hanging wall relative to the footwall give evidence of the stress placed on a rock layer?
Weegy: The position of a hanging wall relative to the footwall gives evidence of the stress placed on a rock layer: When rocks are pulled apart by tension, hanging walls tend to slip below the footwall. [ When rocks are pushed together by compression, hanging walls tend to push above the footwall. target='_blank' rel='nofollow'>http://webcache.googleusercontent.com/search?q=cache:7e_g_fAbgGQJ:' target='_blank' rel='nofollow'>www.powayusd.com/teachers/pfawcett/science/scienceonline/chapter6/chapter6.pdf+&cd=4&hl=en&ct=clnk&gl=ph ] (More)
Question
Expert Answered
Asked 10/18/2013 9:29:49 AM
0 Answers/Comments
When you touch a hot pot or pan, energy moves from the pot to your hand. This is called a. magnetic energy. b. indirect evidence. c. subduction. d. heat transfer.
Question
Not Answered
Updated 8 days ago|11/18/2014 12:24:36 PM
1 Answer/Comment
When you touch a hot pot or pan, energy moves from the pot to your hand. This is called: heat transfer.

Added 8 days ago|11/18/2014 12:24:36 PM
This answer has been confirmed as correct, not copied, and helpful.
Confirmed by jeifunk [11/18/2014 12:29:57 PM]
18,450,198 questions answered
Popular Conversations
Simplify 12A + 2 + A - 1. 14A - 1 13A - 1 13A + 1 User: ...
Weegy: 12(A - B) = 12A - 12B User: Simplify 10x - 3x + (-5x). -2x 2x 18x -18x Weegy: c.18x User: Simplify ...
11/25/2014 3:05:18 PM| 6 Answers
True or false carbohydrates are made up of carton, hydrogen, and ...
Weegy: The answer is True. Here is the source link: User: The two main types of fiber are?
11/25/2014 7:45:43 PM| 5 Answers
x + y = k x - y = k
Weegy: 8 1/3 - 1 5/6 = 25/3 - 11/6; = 50/6 - 11/6; = 39/6; = 13/2; = 6 1/2 User: 5x + y = 6 5x + 3y = -4 Weegy: ...
11/25/2014 9:09:05 AM| 4 Answers
Determine the solution set of (2x - 5)2 = 11.
Weegy: 2x - 3 = 9 2x = 9 + 3 2x = 12 x = 12/2 x = 6 User: Determine the solution set of (3x + 1)2 - 100 = ...
11/25/2014 11:37:07 AM| 4 Answers
The first English child born in the new world
Weegy: TRUE The first English child born in the new world
11/25/2014 1:29:56 PM| 4 Answers
20,000 pounds equals how many English tons?
11/25/2014 3:30:36 AM| 3 Answers
Simplify 20 + (2 + r). r + 22 22r 20r
Weegy: r + 22 User: Simplify (5a)(5b). 10ab 25ab 55ab Weegy: (5a)(5b) = 25ab User: Simplify 7.95 - 3.86 + ...
11/25/2014 8:53:09 AM| 3 Answers
Which personal pronoun best completes the sentence? How is it used? ...
Weegy: My father made my sister and ME blueberry pancakes for breakfast. The correct pronoun is: me; indirect object. ...
11/25/2014 9:42:28 AM| 3 Answers
t Object]User: y + 3 = 2x y + 4 = 3x If you use the comparison ...
Weegy: 31/8 and 25/8 User: What is the result of adding the system of equations? 2x + y = 4 3x - y = 6 x = 2 x = ...
11/25/2014 10:32:36 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: The correct factored form of the given equation x^2 + 3x - 4 = 0 is (x - 1)(x + 4) = 0. User: olve n3 + 2n2 ...
11/25/2014 11:30:00 AM| 3 Answers
Which of the following is the correct factored form of the given ...
Weegy: (x - 3)^2 = 0 written in general form is: x^2 - 6x + 9 = 0 Expand (x - 3)^2 = x^2 - 3x - 3x + 9 = x^2 - 6x + ...
11/25/2014 11:33:47 AM| 3 Answers
Weegy Stuff
S
L
1
L
P
C
1
P
C
1
L
P
C
1
Points 2660 [Total 14370]| Ratings 10| Comments 2560| Invitations 0|Offline
S
L
Points 1435 [Total 3721]| Ratings 0| Comments 1435| Invitations 0|Offline
S
L
Points 777 [Total 1298]| Ratings 6| Comments 717| Invitations 0|Offline
S
1
L
1
L
P
P
L
P
Points 762 [Total 14136]| Ratings 0| Comments 762| Invitations 0|Offline
S
Points 703 [Total 735]| Ratings 1| Comments 693| Invitations 0|Online
S
1
L
L
Points 273 [Total 6667]| Ratings 0| Comments 273| Invitations 0|Offline
S
L
Points 161 [Total 1457]| Ratings 3| Comments 131| Invitations 0|Offline
S
Points 86 [Total 86]| Ratings 1| Comments 76| Invitations 0|Offline
S
Points 50 [Total 50]| Ratings 0| Comments 0| Invitations 5|Offline
S
Points 46 [Total 46]| Ratings 3| Comments 6| Invitations 1|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.